Uncovering Women's Voices: Adrienne Rich's Transformative Poetry and the Power of Liberation - Alheshami, Mugahed Abdulqader Alawi; Sirichum, Jirattikan (Unisia, 2025)
This study aims to examine how Rich uses her poetry to portray silence, voice, and women’s identity in a male-dominated society, explore images of journey and discovery as symbols of both individual and collective freedom, and analyze how her work engages with historical and social issues as a means of empowering women. The selected poems were analyzed through structural and thematic analyses. The results indicate that Rich employed her poetry to criticize women oppression, challenge their silence, and argue the issues of freedom, equality and independence. She used symbols like tigers, guns and galleries to highlight women's oppression and lack of freedom. The use of imagery of travels and explorations focuses on liberation, reclaiming the lost history of women and the possibility of social change. Rich’s poetry is not just a significant subject in feminist literary analysis but in general cultural discourse, since it poses provocative issues on the topics of justice, equality and identity. Her poems prove that literature is one way in which women can reclaim their voices, interrupt the male structures, and build a possibility of social change. Her poetry illustrates how literature has the power to reinstate the voices of women, intervene in the male genres and open up the avenues to social change.